Non-magnetic hard alloy material standard test block, manufacturing method thereof and detection method of nickel pool in non-magnetic hard alloy material

By using paraffin balls to form a nickel pool of specific sizes in standard test blocks of magnetic-free carbide materials, the problem of small and difficult to control the nickel pool is solved, rapid detection and accurate control of the nickel pool is achieved, and the sealing ring is improved Quality and benefits of production.

CN119470666AActive Publication Date: 2025-02-18ZHUZHOU HARD ALLOY GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411455870.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-18
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

In the production process of sealing rings of magnetically-free carbide, the nickel pool is small and difficult to control, resulting in its reflected waves similar to the dirty hole waveform and difficult to distinguish, which in turn affects process control and product quality and leads to economic losses.

Method used

A standard test block production method of magnetic-free carbide material is adopted to form nickel pools of specific diameters and/or depths by using paraffin balls during the sintering process, and the rapid detection of nickel pools is achieved. The method includes measuring the shrinkage coefficient of the magnetically-free alloy material, calculating the size of the pressed blank and paraffin ball, performing compression and over-pressure firing, and finally verifying the size of the nickel pool through precision processing and metallographic slicing technology.

Benefits of technology

It realizes rapid and accurate detection of nickel pools in magnetic-free carbide materials, reduces misleading process control in the production process, and improves the internal quality and economic benefits of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119470666A_ABST
    Figure CN119470666A_ABST
Patent Text Reader

Abstract

The invention relates to a manufacturing method of a non-magnetic hard alloy material standard test block, which comprises the following steps: determining the size of a cylindrical standard test block to be prepared and the diameter and depth of an internal nickel pool of the cylindrical standard test block, and measuring the shrinkage coefficient c of the non-magnetic hard alloy material, the diameter phi 3 and the height h2 of a cylindrical pressed blank, the diameter phi 4 of a paraffin ball and the depth H2 with the pressed face as the reference are calculated according to the shrinkage coefficient c of the non-magnetic hard alloy material, the pressed blank obtained through pressing in a mold is subjected to overpressure burning to obtain a blank, and the standard test block of the non-magnetic hard alloy material is obtained through precision machining. According to the manufacturing method of the non-magnetic hard alloy material standard test block, the nickel pool with the specific diameter and / or depth is formed in the standard test block by migrating metal nickel to the position of the specifically designed paraffin ball in the sintering process. The invention further relates to the non-magnetic hard alloy material standard test block manufactured through the manufacturing method and a rapid detection method for the nickel pool in the non-magnetic hard alloy material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of non-magnetic cemented carbide defect detection, and in particular to a non-magnetic cemented carbide material standard test block and a manufacturing method thereof, and a method for detecting a nickel pool in a non-magnetic cemented carbide. Background Art

[0002] Non-magnetic cemented carbide uses nickel as the bonding phase. It has the characteristics of non-magnetic, high hardness, wear resistance, heat resistance, and corrosion resistance. It is mainly used for equipment accessories working in corrosive environments and is widely used in civilian and military products, such as sealing rings. The quality requirements of sealing rings are high, and the physical and mechanical properties and chemical properties must be stable. These requirements make it difficult to control the production process of non-magnetic cemented carbide, and producers need to have a high level of process control.

[0003] Especially in the actual production process of sealing rings, because nickel is a bonding phase, its carbon range is relatively wide and difficult to control. In addition, due to the need for corrosion resistance, the required chromium content is high, and its performance is even more difficult to control. There are more nickel pools and the third phase appears. Nickel pools will not only affect the performance of the alloy, but also cause the product to have a galvanic cell, resulting in reduced corrosion resistance of the product. Therefore, in the production process of sealing rings, the appearance of nickel pools must be strictly controlled.

[0004] In addition, the size of the nickel pool inside the non-magnetic cemented carbide is very small, most of which are less than 20um. Its reflection wave is similar to the dirty hole waveform, and the two must be distinguished, otherwise it will mislead the process control direction, causing problems in the internal quality of the product and leading to greater economic losses.

[0005] Therefore, it is urgent to develop a rapid detection method for nickel pools in non-magnetic cemented carbide materials. Summary of the invention

[0006] Based on the above, the main purpose of the present invention is to provide a non-magnetic cemented carbide material standard test block and a method for making the same, as well as a method for quickly detecting nickel pools in non-magnetic cemented carbide materials.

[0007] To this end, in a first aspect, the present invention provides a method for making a non-magnetic cemented carbide material standard test block, comprising the following steps:

[0008] S100, determining the diameter φ1 and height h1 of the cylindrical standard test block to be prepared and the diameter φ2 and depth H1 of the nickel pool in the standard test block, wherein φ1>φ2, h1>H, 0.02mm≤φ2≤0.10mm;

[0009] S200, determining the contraction coefficient c of the non-magnetic cemented carbide material, and calculating the diameter φ3 and height h2 of the cylindrical compact, the diameter φ4 of the wax ball and the depth H2 based on the pressing surface according to the contraction coefficient c of the non-magnetic cemented carbide material,

[0010] Among them, φ3=φ1*c, h2=h1*c, φ4=φ2*c, H2=H1*c;

[0011] S300, after partially loading the non-magnetic alloy material powder into the mold, insert a paraffin ball with a diameter of φ4, ensure that the depth of the paraffin ball based on the pressing surface is H2, continue to load the non-magnetic alloy material powder, and after loading, press to obtain a compact;

[0012] S400, the compact obtained in step S300 is subjected to over-pressing and sintering to obtain a cylindrical blank with a diameter of φ1 and a height of h1, wherein the blank has a nickel pool with a diameter of φ2 and a depth of H1;

[0013] S600, performing precision machining on the blank obtained in step S500.

[0014] In the present invention, the shape of the nickel pool is usually spherical in an ideal state, but some deformation may occur during the pressing process. The depth H1 here refers to the depth at the center of the nickel pool.

[0015] In step S500 of the present invention, during the sintering process, the paraffin balls are sintered and decomposed to volatilize into gas, and the molten nickel in the non-magnetic alloy material powder migrates to the position originally occupied by the paraffin to form a nickel pool. It is verified by metallographic sectioning technology that the error between the diameter of the nickel pool in the blank and the set value φ2 is within ±0.01mm, preferably within ±0.002mm, the error between the depth of the nickel pool in the blank and the set value H1 is within ±0.3mm, and the verticality tolerance of the nickel pool in the blank is within 0.1mm.

[0016] In the present invention, the material of the paraffin ball can be gasified into gas and evaporated at a temperature of about 1000° C., without affecting the overall physical and chemical properties of the non-magnetic hard alloy material.

[0017] In the present invention, the rapid detection of the nickel pool in the non-magnetic cemented carbide material depends on the standard test block of the non-magnetic cemented carbide material. Since the size of the nickel pool in the standard test block is very small, at the micron level, and its performance must be ensured at the same time, the production of the nickel pool in the standard test block is a difficult point. The production method of the standard test block of the non-magnetic cemented carbide material provided by the present invention utilizes the migration of metal nickel to the position of the specially designed paraffin balls during the sintering process to form a nickel pool of a specific diameter and / or depth in the standard test block. Thereby, a series of nickel pool ultrasonic detection test blocks with the same diameter and different depths, or a series of nickel pool ultrasonic detection test blocks with the same depth and different diameters are produced.

[0018] As a specific embodiment of the present invention, the non-magnetic cemented carbide material comprises:

[0019] Tungsten carbide WC, 75.4% -84.4%,

[0020] Nickel Ni, 8%-23%,

[0021] Chromium Cr, 0.5%-0.9%,

[0022] Molybdenum, 0.7%-1.1%.

[0023] As a specific embodiment of the present invention, in step S200, the determination of the shrinkage coefficient c of the non-magnetic cemented carbide material includes the following steps: adding the non-magnetic cemented carbide material into a mold for pressing, sintering when no cracks or delamination occurs in the pressed green sheet, and calculating the ratio of the sizes of the non-magnetic cemented carbide material before and after sintering as the shrinkage coefficient.

[0024] As a specific embodiment of the present invention, in step 400, the overpressure sintering conditions include: degumming temperature 300°C-800°C, degumming time 1h-3h, sintering temperature 1340°C-1400°C, sintering time 10h-15h.

[0025] As a specific implementation of the present invention, step S400, the step of selecting wax balls with a diameter of φ4 includes: sieving the wax balls on a sieve and then sieving them through a sieve with a specific mesh size.

[0026] As a specific implementation of the present invention, in step 500, the precision machining includes the following steps: machining the roughness Ra of the upper and lower surfaces of the blank to 3.0 μm-4.0 μm.

[0027] To this end, in a second aspect, the present invention provides a standard test block of non-magnetic alloy material containing a nickel pool manufactured using the above-mentioned manufacturing method.

[0028] To this end, in a third aspect, the present invention provides a method for rapid detection of nickel pools in non-magnetic alloy materials, comprising the following steps:

[0029] S10, using the above-mentioned manufacturing method to manufacture a series of cylindrical non-magnetic hard alloy material standard test blocks with the same diameter φ1 and height h1, wherein the nickel pools in each non-magnetic hard alloy material standard test block have the same diameter φ2 and different depths;

[0030] S20, using ultrasonic waves to test the nickel pool in each standard test block of non-magnetic cemented carbide material, and establishing a DAC curve chart by reading the nickel pool attenuator at different depths with the same diameter;

[0031] S30, using ultrasonic waves to test the nickel pool in the sample to be tested, reading the nickel pool attenuator under the same diameter φ2, and calculating the nickel pool depth H of the sample to be tested from the DAC curve.

[0032] As a specific implementation of the present invention, preferably, in step S20, the ultrasonic test uses an ultrasonic flaw detector with an RF mode, and the probe is a 2MHz-15MHz straight probe.

[0033] To this end, in a fourth aspect, the present invention provides a method for rapid detection of nickel pools in non-magnetic alloy materials, comprising the following steps:

[0034] S1. A series of cylindrical non-magnetic hard alloy material standard test blocks with the same diameter φ1 and height h1 are manufactured by the above manufacturing method. The nickel pools in each non-magnetic hard alloy material standard test block have the same depth H1 and different diameters.

[0035] S2. Use ultrasonic waves to test the nickel pool in each standard test block of non-magnetic alloy material, and establish a DAC curve chart by reading the nickel pool attenuator at different diameters at the same depth;

[0036] S3. Use ultrasonic waves to test the nickel pool in the sample to be tested, and calculate the nickel pool diameter φ of the sample to be tested from the DAC curve through the nickel pool attenuator reading at the same depth H1.

[0037] As a specific implementation of the present invention, preferably, in step S2, the ultrasonic test uses an ultrasonic flaw detector with an RF mode, and the probe is a 2MHz-15MHz straight probe.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] 1. The method for making a standard test block of non-magnetic cemented carbide material provided by the present invention utilizes the migration of metal nickel to the position of the original wax ball during the sintering process to form a nickel pool with a specific diameter and / or depth. Thus, a series of nickel pool ultrasonic detection test blocks with the same diameter and different depths, or a series of nickel pool ultrasonic detection test blocks with the same depth and different diameters can be made. Thus, a nickel pool DAC curve chart can be made using a complete set of ultrasonic detection test blocks developed, and this chart can be used to quickly determine the size of the nickel pool found in the detection.

[0040] 2. The method for making the non-magnetic hard alloy material standard test block provided by the present invention is simple, efficient and economical.

[0041] 3. The method for making a standard test block of non-magnetic cemented carbide material provided by the present invention can promote the development of non-destructive ultrasonic testing technology and the development of non-magnetic cemented carbide production technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 A physical picture of a paraffin wax ball with a specific diameter.

[0043] Figure 2 This is a physical picture of the non-magnetic cemented carbide material standard test block made in Example 1.

[0044] Figure 3This is a metallographic picture of the nickel pool found using the metallographic sectioning technique in Example 1. The diameter of the nickel pool is 52 μm.

[0045] Figure 4 This is a metallographic picture of the nickel pool found using the metallographic sectioning technique in Example 2. The diameter of the nickel pool is 41.2 μm.

[0046] Figure 5 It is a DAC curve diagram established using a series of non-magnetic cemented carbide material standard test blocks (the nickel pool in each standard test block has the same diameter but different depths).

[0047] Figure 6a This is a detection diagram of the nickel pool of the test sample 1 by ultrasonic detection.

[0048] Figure 6b It is the nickel cell size of the nickel cell of the test sample 1 determined by using the DAC curve diagram.

[0049] Figure 7a This is a detection diagram of the nickel pool of the test sample 2 by ultrasonic detection.

[0050] Figure 7b It is the nickel cell size of the nickel cell of the test sample 2 determined by using the DAC curve diagram. DETAILED DESCRIPTION

[0051] The technical scheme of the present invention is further described below by specific embodiments. Those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0052] Example 1

[0053] This embodiment provides a method for making a non-magnetic cemented carbide material standard test block, and the specific steps are as follows:

[0054] (1) The non-magnetic hard alloy material standard test block prepared in this embodiment is cylindrical, with a diameter of φ1 (50 mm) and a height of h1 (100 mm); the diameter of the nickel pool in the standard test block is φ2 (0.05 mm) and a depth of H1 (50 mm);

[0055] (2) Select a non-magnetic alloy material, the composition of the non-magnetic alloy material is:

[0056] Tungsten carbide WC, 84.4%,

[0057] Nickel Ni, 14.1%,

[0058] Chromium Cr, 0.7%,

[0059] Molybdenum, 0.8%.

[0060] (3) Determine the shrinkage coefficient c of the non-magnetic alloy material: weigh 1 kg of the non-magnetic mixture and press it. When there are no cracks or delamination in the pressed block, the diameter of the pressed block is 20 mm and the height is 50 mm. After sintering (debonding temperature 500° C., debonding time 1.5 hours, sintering temperature 1400° C., sintering time 13.5 hours), the diameter of the pressed block is 16 mm and the height is 40 mm. After calculation, c=1.25;

[0061] (4) Calculate the diameter φ3 and height h2 of the cylindrical green compact, the diameter φ4 of the wax ball and the depth H2 based on the pressing surface according to the shrinkage coefficient c of the preferred non-magnetic alloy material.

[0062] φ3=φ1*c=62.5mm, h2=h1*c=125mm,

[0063] φ4=φ2*c=0.0625mm, H2=H1*c=50*1.25=62.5mm;

[0064] (5) 1 kg of spherical paraffin particles were sieved for 0.5 hours, first through a 230-mesh sieve and then through a 200-mesh sieve to select spherical paraffin particles with a diameter of 0.0625 mm (see Figure 1 shown);

[0065] (6) Load the non-magnetic cemented carbide material powder into the inner cavity of the mold. When half of the powder is loaded, load the spherical paraffin particles selected in step (5) into the inner cavity of the mold so that its depth H2 is 62.5 mm based on the pressing surface. Continue to load the non-magnetic cemented carbide material. After the non-magnetic cemented carbide material is loaded, press it. The pressed green compact is cylindrical with a diameter of φ3 = 62.5 mm and a height of h2 = 125 mm.

[0066] (7) The compacted green sheet obtained in step (6) is subjected to press sintering (debinding first and then sintering, debinding temperature is 500° C., debinding time is 1.5 hours, sintering temperature is 1400° C., and sintering time is 13.5 hours) to obtain a cylindrical green sheet with a diameter of φ1 and a height of h1;

[0067] (8) The blank is processed so that the roughness Ra of the upper and lower surfaces (two circular surfaces of the cylinder) is 3.2 μm, which is convenient for subsequent flaw detection and obtains a standard test block of non-magnetic cemented carbide material (see Figure 2 shown);

[0068] (9) The diameter of the nickel pool in the standard test block is 52 μm (see Figure 3As shown), the difference between the diameter of the nickel pool in the standard test block and the set value is 0.002mm, the difference between the depth of the nickel pool in the standard test block and the set value is 0.1mm, and the verticality tolerance of the nickel pool in the standard test block is 0.1mm.

[0069] Example 2

[0070] This embodiment provides a method for making a non-magnetic cemented carbide material standard test block, and the specific steps are as follows:

[0071] (1) The non-magnetic hard alloy material standard test block prepared in this embodiment is cylindrical, with a diameter of φ1' (50 mm) and a height of h1' (100 mm); the diameter of the nickel pool in the standard test block is φ2' (0.04 mm) and a depth of H1' (50 mm);

[0072] (2) and (3) are the same as in Example 1;

[0073] (4) Calculate the diameter φ3' and height h2' of the cylindrical green compact, the diameter φ4' of the wax ball and the depth H2' based on the pressing surface according to the shrinkage coefficient c of the preferred non-magnetic alloy material.

[0074] φ3'=φ1'*c=62.5mm, h2'=h1'*c=125mm,

[0075] φ4'=φ2'*c=0.05mm, H2'=H1'*c=50*1.25=62.5mm;

[0076] (5) 1 kg of spherical paraffin wax particles were selected and sieved for 0.5 hours, first through a 270-mesh sieve and then through a 230-mesh sieve to select spherical paraffin wax with a diameter of 0.05 mm;

[0077] (6) placing the non-magnetic cemented carbide material and the spherical paraffin particles in a mold and pressing them (same as in Example 1);

[0078] (7) The pressed green compact is subjected to press sintering (debinding first and then sintering, debinding temperature is 500° C., debinding time is 1.5 hours, sintering temperature is 1400° C., and sintering time is 13.5 hours) to obtain a cylindrical green compact with a diameter of φ1′ and a height of h1′;

[0079] (8) Precision machining the blank (machining requirements are the same as those in Example 1) to obtain a non-magnetic cemented carbide material standard test block;

[0080] (9) Verified by metallographic sectioning technology, see Figure 4The diameter of the nickel pool in the standard test block is 41.2μm. The difference between the diameter of the nickel pool in the standard test block and the set value is 0.0012mm, the difference between the depth of the nickel pool in the standard test block and the set value is 0.3mm, and the verticality tolerance of the nickel pool in the standard test block is 0.1mm.

[0081] Example 3

[0082] This embodiment provides a method for making a standard test block of non-magnetic cemented carbide material. The specific steps are as follows:

[0083] (1) The non-magnetic hard alloy material standard test block prepared in this embodiment is cylindrical, with a diameter of φ1" (50 mm) and a height of h1" (100 mm); the diameter of the nickel pool in the standard test block is φ2" (0.03 mm) and a depth of H" (50 mm);

[0084] (2) and (3) are the same as in Example 1;

[0085] (4) Based on the shrinkage coefficient c of the preferred non-magnetic alloy material, calculate the diameter φ3" and height h2" of the cylindrical compact, the diameter φ4" of the wax ball and the depth H2" based on the pressing surface.

[0086] φ3”=φ1”*c=62.5mm, h2”=h1”*c=125mm,

[0087] φ4”=φ2”*c=0.0375mm, H2”=H1’*c=50*1.25=62.5mm;

[0088] (5) 1 kg of specific paraffin wax particles were selected and sieved for 0.5 hour, first through a 400-mesh sieve and then through a 325-mesh sieve to select spherical paraffin wax with a diameter of 0.0375 mm;

[0089] (6) placing the non-magnetic cemented carbide material and the spherical paraffin particles in a mold and pressing them (same as in Example 1);

[0090] (7) The pressed green compact is subjected to over-pressing sintering (the over-pressing sintering conditions are the same as those in Example 1) to obtain a green compact with a diameter of φ1″ and a height of h1″;

[0091] (8) The blank is precision machined (the machining requirements are the same as those in Example 1) to obtain a standard test block of non-magnetic cemented carbide material.

[0092] Test Example 1

[0093] A series of standard test blocks of non-magnetic alloy materials (cylindrical, with a diameter of φ of 150 mm and a height of h1 of 100 mm) were prepared by the method of Example 1. The nickel pools inside had the same diameter of 0.05 mm and different depths of 15 mm, 25 mm, 35 mm, 45 mm, 55 mm, 65 mm, and 75 mm.

[0094] The ultrasonic 5 MHz probe and 10 MHz probe were used to test this series of non-magnetic alloy material standard test blocks, and the results were Figure 5 Middle φ0.05mm curve (solid line corresponds to 5M probe, dashed line corresponds to 10M probe). Figure 5 The horizontal axis distance represents the depth, and the vertical axis amplitude (unit db) represents the reading of the instrument attenuator.

[0095] Using the same method as above, we can obtain Figure 5 The φ0.04mm curve, φ0.03mm curve and φ0.02mm curve.

[0096] During the testing of the product 1, the ultrasonic test found a nickel pool inside the product 1 (see Figure (6a)). According to the waveform, the depth H of the nickel pool can be measured to be 66mm, and the attenuator reading is 53dB. Figure 5 , we can see that the diameter of this nickel pool is 33 μm (see Figure 6b ).

[0097] During the testing of the product 2, ultrasonic testing revealed a nickel pool inside the product 2 (see Figure (7a)). Figure 5 The diameter of the nickel pool is determined to be 40 μm (see Figure 7b ).

[0098] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for making a standard test block of non-magnetic cemented carbide material, characterized in that: The following steps are involved: S100, determining the diameter φ1 and height h1 of the cylindrical standard test block to be prepared and the diameter φ2 and depth H1 of the nickel pool in the standard test block, wherein φ1>φ2, h1>H, 0.02mm≤φ2≤0.10mm; S200, determining the contraction coefficient c of the non-magnetic cemented carbide material, and calculating the diameter φ3 and height h2 of the cylindrical compact, the diameter φ4 of the wax ball and the depth H2 based on the pressing surface according to the contraction coefficient c of the non-magnetic cemented carbide material, Among them, φ3=φ1*c, h2=h1*c, φ4=φ2*c, H2=H1*c; S300, after partially loading the non-magnetic alloy material powder into the mold, insert a paraffin ball with a diameter of φ4, ensure that the depth of the paraffin ball based on the pressing surface is H2, continue to load the non-magnetic alloy material powder, and after loading, press to obtain a compact; S400, the compact obtained in step S300 is subjected to over-pressing and sintering to obtain a cylindrical blank with a diameter of φ1 and a height of h1, wherein the blank has a nickel pool with a diameter of φ2 and a depth of H1; S600, performing precision machining on the blank obtained in step S500.

2. The method according to claim 1, characterized in that: The non-magnetic hard alloy material comprises: Tungsten carbide WC, 75.4% -84.4%, Nickel Ni, 8%-23%, Chromium Cr, 0.5%-0.9%, Molybdenum, 0.7%-1.1%.

3. The production method according to claim 1 or 2, characterized in that: In step S200, the determination of the shrinkage coefficient c of the non-magnetic cemented carbide material includes the following steps: adding the non-magnetic cemented carbide material into a mold for pressing, sintering when the pressed green body has no cracks or delamination, and calculating the ratio of the sizes of the non-magnetic cemented carbide material before and after sintering as the shrinkage coefficient.

4. The method according to any one of claims 1 to 3, characterized in that: In step 400, the overpressure sintering conditions include: degumming temperature 300°C-800°C, degumming time 1h-3h, sintering temperature 1340°C-1400°C, and sintering time 10h-15h.

5. The method according to any one of claims 1 to 4, characterized in that: Step S400, the step of selecting wax balls with a diameter of φ4 includes: sieving the wax balls on a sieve and then sieving them through a sieve with a specific mesh size.

6. The method according to any one of claims 1 to 5, characterized in that: In step 500, the precision machining includes the following steps: machining the roughness Ra of the upper and lower surfaces of the blank to 3.0 μm-4.0 μm.

7. A non-magnetic hard alloy material standard test block containing a nickel pool made using the making method described in any one of claims 1 to 6.

8. A rapid detection method for nickel pools in non-magnetic hard alloy materials, characterized in that: The following steps are involved: S10. A series of cylindrical non-magnetic hard alloy material standard test blocks having the same diameter φ1 and height h1 are manufactured by the manufacturing method described in any one of claims 1 to 6, wherein the nickel pools in each non-magnetic hard alloy material standard test block have the same diameter φ2 and different depths; S20, using ultrasonic testing of each non-magnetic hard alloy material standard test block, and establishing a DAC curve graph by reading the nickel pool attenuator at different depths with the same diameter; S30, using ultrasonic waves to test the nickel pool in the sample to be tested, reading the nickel pool attenuator under the same diameter φ2, and calculating the nickel pool depth H of the sample to be tested from the DAC curve.

9. A rapid detection method for nickel pools in non-magnetic hard alloy materials, characterized in that: The following steps are involved: S1. A series of cylindrical non-magnetic hard alloy material standard test blocks having the same diameter φ1 and height h1 are manufactured by the manufacturing method described in any one of claims 1 to 6, wherein the nickel pools in each non-magnetic hard alloy material standard test block have the same depth H1 and different diameters; S2. Use ultrasonic waves to test the nickel pool in each standard test block of non-magnetic alloy material, and establish a DAC curve chart by reading the nickel pool attenuator at different diameters at the same depth; S3. Use ultrasonic waves to test the nickel pool in the sample to be tested, and calculate the nickel pool diameter φ of the sample to be tested from the DAC curve through the nickel pool attenuator reading at the same depth H1.

10. The detection method according to claim 8 or 9, characterized in that: In step S20 and step S2, the ultrasonic tests are the same or different, and each independently uses an ultrasonic flaw detector with RF mode, and the probe is a 2MHz-15MHz straight probe.

Citation Information

Patent Citations

  • Manufacturing method of hard alloy ultrasonic testing flat-bottom hole test block

    CN112362757A

  • Ultrasonic detection reference block for simulating natural defects and manufacturing method thereof

    CN117871667A

  • Cemented carbide employing a refractory metal binder and process for producing same

    US3964878A

  • Corrosion resistant nickel base alloy

    US5424029A